2003
DOI: 10.1046/j.1540-8175.2003.03024.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Three‐Dimensional Color Flow Doppler: An Improved Technique for the Assessment of Mitral Regurgitation

Abstract: Three-dimensional imaging of mitral regurgitant jets is feasible in the majority of patients. This improved technique provides additional information to that obtained from the 2D examination. Particularly, in patients with paravalvular leaks 3D color flow Doppler provides information on the origin and the extent of the dehiscence, as well as insight into the jet direction. In addition, in patients with eccentric mitral regurgitation, this new modality overcomes the inherent limitations of 2D echo Doppler by de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 12 publications
0
30
0
Order By: Relevance
“…1). For example, several studies have employed 3D echo to demonstrate that functional MR involves annular dilatation, chordal tethering by displaced papillary muscles, and measurable systolic tenting of the mitral leaflets [1][2][3][4]. These studies have also demonstrated that the crescent-shaped leaflet coaptation defect of functional MR may be very different for the more circular or elliptical defect encountered with organic (degenerative or myxomatous) valve disorders [5••, 6].…”
Section: Valve Morphology and Dysfunctionmentioning
confidence: 99%
“…1). For example, several studies have employed 3D echo to demonstrate that functional MR involves annular dilatation, chordal tethering by displaced papillary muscles, and measurable systolic tenting of the mitral leaflets [1][2][3][4]. These studies have also demonstrated that the crescent-shaped leaflet coaptation defect of functional MR may be very different for the more circular or elliptical defect encountered with organic (degenerative or myxomatous) valve disorders [5••, 6].…”
Section: Valve Morphology and Dysfunctionmentioning
confidence: 99%
“…8,9 In addition, improved assessment of anatomy and function of valves was achieved through better detail (figure 1), as well as the first time use of 3D colour flow jets. [10][11][12][13] With further advancements in technology, a transition from stepwise to continuous rotational scanning was achieved, offering the possibility of acquiring a complete 3D dataset within a single breath-hold of ten seconds. However, equal to freehand imaging there was still the necessity to interpolate between essentially multiple 2D images, making the technique sensitive to motion artefacts by involuntary movement of heart and lungs.…”
Section: Three-dimensional Echocardiographic Techniquesmentioning
confidence: 99%
“…3DE quantifi cation of color fl ow has recently been validated in adults by comparison with cardiac outputs obtained by thermodilution [ 42 ]. Application of this technique to pathologic states could lead to potentially more accurate measurements of regurgitant volumes and fractions [ 43 ].…”
Section: Visualizing and Quantifying 3de Color Fl Owmentioning
confidence: 99%